Analysis of Cadmium (Cd) Heavy Metal Content in Headsnake Fish (Channa striata) Derived from Rawa Taliwang Lake, West Sumbawa Regency 2021 - Karina Legiarsi; Khairuddin Khairuddin; M. Yamin (Jurnal Biologi Tropis, 2022)
Fish is one of the aquatic organisms that is often used as a biological indicators of heavy metals in waters. The purpose of the research about analysis of cadmium (Cd) heavy metal content in headsnake fish (Channa striata) derived from Rawa Taliwang Lake, West Sumbawa Regency 2021 is to determine the cadmium in headsnake fish from Rawa Taliwang Lake. The research was conducted for 2 months, starting from September-October 2021. Sampling was carried out by purposive sampling at 2 research stations. Fish samples were taken 2 fishes at each station using gill nets and plaited rattan fish trap. The fish species taken were headsnake fish. The research sample was then analyzed in the West Nusa Tenggara Health, Testing and Calibration Laboratory. The data analysis was carried out by taking muscle tissue from headsnake fish and then analyzing the content of heavy metal in the from cadmium using AAS (Atomic Absorbtion Spectrophotometry). The measurement result showed that heavy metal content of cadmium in headsnake fish from Rawa Taliwang Lake ranged from 0,115 mg/kg (ppm) to 0,161 mg/kg (ppm). This shows that Rawa Taliwang Lake has been contaminated by cadmium exceeds the threshold set by Food and Drug Supervisory Agency (BPOM) No.5 of 2018 concerning the Maximum Limit of Heavy Metal Contamination in Processed Food which is 0,1 mg/kg.